An Artificial Intelligence (AI) Research-Doing Approach for Higher Education (Global Journal of Human-Social Science, 2024)
The 21st Century has changed like no other centuries the human society s development on unprecedent scale Is the century of technological advances such Artificial Intelligence AI that is currently hard-pressing the field of research-doing at Higher Education beyond human intellectual capabilities This can change the future of this educational field As it is becoming a global education phenomenon The study aims to present an outlook about the impact of Artificial Intelligence AI into academia research An interdisciplinary approach based on prior trustworthy researchworks results has been used to address the research hypotheses and answer their respective questions A qualitative methodology has been used to accomplish the aim This research criterium involved a theory triangulation the reviewing of academic and scientific research works books and Internet accredited websites These materials are related to the subject matter presented The study results are beneficial for academicians involved in educational AI academia research-doing towards global education perspectives
Keywords: artificial intelligence (AI); AI research tools; technology disparity; demography statistic